PENDAMPINGAN BELAJAR MATEMATIKA SISWA KELAS VIII C MTs S MODERN ARAFAH MATERI PERSAMAAN GARIS MELALUI DUA TITIK - Norhaslina, Norhaslina; Hesti, Nadiya; Andina, Andina; Putra, Aan (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The aim of this assistance is to improve understanding and skills for students who have difficulty learning mathematics, especially in the material